Exogenous gibberellins inhibit coffee (Coffea arabica cv. Rubi) seed germination and cause cell death in the embryo - da Silva, E A Amaral (Journal of experimental botany, 2005)
The mechanism of inhibition of coffee (Coffea arabica cv. Rubi) seed germination by exogenous gibberellins (GAs) and the requirement of germination for endogenous GA were studied. Exogenous GA(4+7) inhibited coffee seed germination. The response to GA(4+7) showed two sensitivity thresholds: a lower one between 0 and 1 microM and a higher one between 10 and 100 microM. However, radicle protrusion in coffee seed depended on the de novo synthesis of GAs. Endogenous GAs were required for embryo cell elongation and endosperm cap weakening. Incubation of coffee seed in exogenous GA(4+7) led to loss of embryo viability and dead cells were observed by low temperature scanning microscopy only when the endosperm was surrounding the embryo. The results described here indicate that the inhibition of germination by exogenous GAs is caused by factors that are released from the endosperm during or after its weakening, causing cell death in the embryo and leading to inhibition of radicle protrusion